Ex situ hypothermic perfusion of nonhuman primate pancreas: A feasibility study. Issue 7 (24th February 2020) - Prudhomme, Thomas; Renaudin, Karine; Lo Faro, Maria Letizia; Cantarovich, Diego; Kervella, Delphine; Minault, David; Hervouet, Jérémy; Le Bas‐Bernardet, Stéphanie; Karam, Georges; Blancho, Gilles; Branchereau, Julien
Abstract: Pancreatic static cold storage (SCS) is the gold‐standard method for pancreas preservation. Our main objective was to evaluate feasibility of hypothermic perfusion (HP) of nonhuman primates' pancreases for potential organ transplantation. Seven baboon pancreases were tested. Animals were included in a study approved by the French Research Ministry of Health. Two groups were compared: the control group (n = 2) was preserved using conventional SCS for 24‐h and the perfusion group (n = 5) used HP for 24‐h, with three different perfusion pressures (PP): 15 (n = 3), 20 (n = 1), and 25 mm Hg (n = 1). In the control group, focal congestion of islets was observed after 6‐h. At 24‐h, ischemic necrosis and multifocal congestion also occurred. In the HP group, at 15 mm Hg PP, multifocal congestion of islets was present at 24‐h. At 20 mm Hg PP, no ischemic necrosis was found after 6‐h. At 12‐h and 24‐h, focal congestion of islets was seen. At 25 mm Hg PP, focal congestion of islets appeared after 12‐h. Immunostaining for insulin, glucagon, and somatostatin was normal and similar in controls and perfused pancreas transplants even after 24‐h. Apoptosis index represented by cleaved caspase 3 activity, was less than 1% in perfusion and control groups, even after 24‐h. HP of nonhuman primate pancreas is feasible and not deleterious as far as 24‐h compared to SCS. SCS for more than 12‐h was harmful for the transplants. Systolic perfusion pressure between 15‐20 mm Hg did not cause any pathological injury of the tested organs.